2013
DOI: 10.1016/j.joms.2012.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistological Features in Adenomatoid Odontogenic Tumor: Review of the Literature and First Expression and Mutational Analysis of β-Catenin in This Unusual Lesion of the Jaws

Abstract: Purpose: To investigate for the first time the immunohistochemical and mutational status of b-catenin in a mandibular case of adenomatoid odontogenic tumor (AOT) and to review the immunohistochemical expression data of various markers (cytokeratins, metalloproteinases, etc) in such a lesion. Materials and Methods:A case of follicular-type AOT in a young male patient was analyzed in regard to the immunohistochemical expression of b-catenin and mutations of the b-catenin gene (CTNNB1). Its expression is altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
(41 reference statements)
1
16
0
Order By: Relevance
“…According to the literature, AOTs have shown CK5, CK14, CK17 and CK19 positivity, which is similar to the cytokeratin profile of dentigerous cyst and oral gingival epithelium. In addition, the non-aggressive nature of the AOT is supported by low expression of proliferative markers such as PCNA and Ki-67 [15]. In accordance with the literature, similar CK 19 expression patterns and low Ki-67 expression were observed in our cases as well.…”
Section: Discussionsupporting
confidence: 92%
“…According to the literature, AOTs have shown CK5, CK14, CK17 and CK19 positivity, which is similar to the cytokeratin profile of dentigerous cyst and oral gingival epithelium. In addition, the non-aggressive nature of the AOT is supported by low expression of proliferative markers such as PCNA and Ki-67 [15]. In accordance with the literature, similar CK 19 expression patterns and low Ki-67 expression were observed in our cases as well.…”
Section: Discussionsupporting
confidence: 92%
“…Beta‐catenin, a member of the Wnt signaling pathway, plays an important role in dental development and also plays in epithelial cell‐to‐cell adhesion. Harnet et al () demonstrated an absence of nuclear expression but a strong cytoplasmic and membranous staining of the columnar and cuboidal cells of duct‐like structures and solid nodules within the follicular type of AOT, claiming their results were in agreement with the benign clinical behavior and nature of the AOT when comparing similar studies of beta‐catenin expression in ameloblastomas.…”
Section: Resultsmentioning
confidence: 80%
“…The #MeSH words used were adenomatoid odontogenic tumor, odontogenic, and case report. We reviewed the data associated with AOT from 2000 to 2014,[3456781314151617181920212223242526272829303132333435363738394041424344454647484950515253545556575859606162636465666768697071727374757677787980818283848586878889919293] and it was found that in the last 14 years, there was a record of 255 reported cases.…”
Section: Discussionmentioning
confidence: 99%